Implementation of Blog-Based Learning Media: Community Service for Elementary School Teachers - Kartikasari, Erlin; Suryarini, Diah Yovita (Journal of Education Method and Learning Strategy, 2023)
Elementary schools in Driyorejo Gresiks consist of 11 private elementary schools and 26 public elementary schools. The location of the school is mostly located in rural areas and most teachers are rarely involved in scientific activities carried out by universities, so that the knowledge and understanding of teachers is still not related to learning media or other learning innovations. The results of interviews obtained from several teachers in public and private elementary schools at UPTD Driyorejo, Gresik Regency obtained information that some teachers almost never use blog-based  learning media  because the media does not exist and the ability of teachers to develop it is also lacking. This has an impact on the implementation of learning activities that take place less meaningfully and tend to be rote in nature. The use of blog-based  learning  is expected to increase teacher innovation, motivate, and increase student achievement optimally.  Community service is carried out by conducting training on the implementation of blog-based learning  media.  The training implementation stage is carried out in two sessions.  The first session explained the  blog-based learning media material. Second session of  training iimplementation of blog-based learning media for elementary school teachers in Driyorejo Gresik.